2009
DOI: 10.1097/ftd.0b013e31819c7037
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Exposure and the Impact of Smoking and Gender: A Population Pharmacokinetic Study

Abstract: The primary objective of this study was to evaluate the magnitude and variability of concentration exposure to clozapine and norclozapine in a real-world clinical setting, with a focus on smoking status, using population pharmacokinetic methodologies. A retrospective review of plasma clozapine and norclozapine concentrations taken from inpatients at the Centre for Addiction and Mental Health, Toronto, from 2001 to 2007 was conducted. A nonlinear mixed-effects model was developed using NONMEM, including age, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 46 publications
3
64
0
2
Order By: Relevance
“…We built a combined structural model to explain the conversion of clozapine into norclozapine (Figure 1) based on the metabolism of clozapine. Therefore, in the current study, we assumed that clozapine was partly converted into norclozapine with a conversion fraction (KF), which was more reasonable than the assumption in previous PPK studies with respect to the process of clozapine metabolism [11,15,29] . The model proposed in this study provided an adequate fit to the data for both clozapine and norclozapine.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We built a combined structural model to explain the conversion of clozapine into norclozapine (Figure 1) based on the metabolism of clozapine. Therefore, in the current study, we assumed that clozapine was partly converted into norclozapine with a conversion fraction (KF), which was more reasonable than the assumption in previous PPK studies with respect to the process of clozapine metabolism [11,15,29] . The model proposed in this study provided an adequate fit to the data for both clozapine and norclozapine.…”
Section: Discussionmentioning
confidence: 94%
“…It was reported that smoking can increase the clearance of clozapine and that the sudden cessation of smoking can cause a significant decrease in caffeine clearance (P<0.01) of 36.1% [32][33][34] . Sex was also reported to be a significant covariate affecting the clearance of clozapine and norclozapine [11,35,36] . Previous studies have shown that CYP1A2 activity was lower in females than in males [37] , whereas other studies found no differences in CYP1A2 activity between males and females and insisted that smoking could induce CYP1A2 activity and reduce clozapine clearance [33,38] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some published studies support an age effect on plasma antipsychotic levels, this has not been a consistent finding [46•,47,48]. For example, we conducted a population pharmacokinetic study to evaluate the effects of age on oral clearance of clozapine and norclozapine, using a total of 519 plasma clozapine concentrations from 197 patients that were collected through routine therapeutic drug monitoring [48]. Our data demonstrated that while smoking and male sex were associated with increased oral clearance, age did not have any impact on the clearance of clozapine or norclozapine.…”
Section: Potential Mechanisms Of Age-related Increased Sensitivity Inmentioning
confidence: 99%